Pengaruh Komunikasi Internal Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Cv. Baby Ministry Indonesia Bsd Tangerang Selatan - Leny Rahmawati; Heri Priyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This research aims to determine the influence of Internal Communication and Work Discipline on employee performance at CV. Baby Ministry Indonesia BSD South Tangerang City. The research method uses quantitative methods through an associative approach. The population in this study was 30 respondents. The sampling technique used was non-probability sampling or saturated sampling, so the sample in this study was 30 respondents. Analysis in the research used the SPSS (Statistical Package For Social Science) program version 28.0. Data instrument testing (validity test and reliability test). Classic assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test). Quantitative analysis techniques (simple linear regression test, multiple linear regression test, correlation coefficient test and coefficient of determination test). Hypothesis testing (t test and f test). The results of the research show that Internal Communication has a positive and significant influence on employee performance where the calculated t value > t table or (2.656 > 2.048) is obtained and is strengthened by the ρ value < Sig.0.05 or (0.013 < 0.05). Work Discipline has a positive and significant influence on employee performance where the calculated t value > t table or (10.910 > 2.048) is obtained. and reinforced with a ρ value < Sig.0.05 or (0.000 < 0.05). Internal Communication and Work Discipline have a positive and significant influence on employee performance where the calculated f value > f table or (64.463 > 3.350) is obtained. This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05) . Based on the results of the f test (simultaneous test). The results of the determination test show an R square value of 0.827, which means that the Internal Communication and Work Discipline variables can contribute 82.7% to employee performance. while the remaining amount was (100-82.7%) = 17.3% influenced by other factors that were not researched.